The quest for argumentative equivalence : argumentative patterns in political interpreting contexts - Brambilla, Emanuele, 1964- (Argumentation in context, 2018)
What are the implications of strategic manoeuvring for the activity of the simultaneous interpreter? This is the main question addressed in 'The Quest for Argumentative Equivalence'. Based on the analysis of a multilingual comparable corpus named ARGO, the book investigates political argumentation with an eye to its reformulation by interpreters. After reporting and discussing a series of case studies illustrating interpreters' problems in the political context, the study reconstructs the prototypical argumentative patterns used by Obama, Cameron, Sarkozy and Hollande not only in a hermeneutical perspective, but also considering interpreters' need to reproduce them into a foreign language. Situated at the intersection of Argumentation Theory and Interpreting Studies, the book provides a contribution to the descriptive study of political argumentation, highlighting the presence of interpreters as a key contextual variable in political communication and deepening the study of the interlinguistic and translational implications of the act of arguing.